Cyclic plastic behavior of dovetail under fretting load. (September 2015) - Wei, Da-Sheng; Shi, Liang; Wang, Yan-Rong
Highlights: A Chaboche constitutive model is established to describe the plastic behavior. The contact stress along the contact surface and its normal direction are obtained. Evolution law of contact stress and strain with cyclic loading is obtained. Abstract: The high gradient stresses near the edge of contact zone in dovetail assemblies will result in the appearance of a small plastic zone, which makes it difficult to calculate the contact stresses accurately. These calculated stresses are the premise to evaluate the strength of dovetail assemblies, but the majority of previous research on the solution of contact stresses have been usually carried out under linear elastic conditions. Thus this study focuses on characterizing the plasticity occurred in the dovetail assemblies under cyclic loading. A viscoplastic constitutive model of the titanium alloy TC4 is established based on the Chaboche theory. Furthermore, the calculation of contact stresses is carried out by use of the finite element method (FEM) with the constitutive model. The distribution feature of the contact stresses along the contact surface and the depth direction is obtained. The results show that the cyclic stress characteristics i.e. stress gradient, cyclic peak stress, and stress ratio, are not the same at different locations, namely different nodes of the FE model along the contact surface and the depth direction. These differences would make it more difficult to select suitable parameters for life prediction and to identify the most important effect factor. It is meaningful that the results of the study could provide some useful data and an idea for obtaining suitable parameters in fretting fatigue life prediction. The life prediction method with the effect of stress gradient considered may become an efficient approach to predict the fretting fatigue life of dovetail assemblies.